Mazhab Tafsir Syi’ah-Tafsir Yang Menolak Jadi Bayangan - Siti Mudthiya Arpijayanti; Akhmad Dasuki (STAI KH. MUHAMMAD ALI SHODIQ TULUNGAGUNG, 2025)
The tradition of Qur’anic exegesis in Islam has long been dominated by Sunni approaches, often marginalizing interpretations from the Shi’a school. However, Shi’a tafsir possesses its own independent epistemological foundation, rooted in the spiritual authority of Ahl al-Bayt as the authentic interpreters of revelation. This study aims to explore the characteristics of exegetical schools within Shi’a tradition by highlighting their sources, methods, prominent figures, and the role of tafsir as a discourse of resistance against mainstream interpretive dominance. Employing a qualitative approach based on textual analysis and discourse study, this research focuses on classical tafsir within the Imami Shi’a school. The findings show that Shi’a exegesis has developed through narrative-tradition-based (bi al-ma’tsur), philosophical-esoteric (falsafi-isyari), and thematic (mawdu‘i) approaches, centering on concepts such as imamate, wilāyah, and divine justice (‘adl). Tafsir also functions as a tool for identity formation and critique of religious-political hegemony, particularly in contexts such as Iran, Iraq, and Lebanon. In conclusion, Shi’a tafsir is not merely an interpretive tradition but also a space of discursive resistance and theological-political expression. Exploring Shi’a exegesis is essential to foster inter-sectarian dialogue and enrich the inclusive landscape of Islamic scholarship. Keywords : Shi’a Exegete, discursive resistance, inter-sectarian dialogue